The effect of gender, age and sports specialisation on isometric trunk strength in Greek high level young athletes - Tsolakis, C.; Simeonidis, T.; Georginis, P.; Cherouveim, E.; Methenitis, S.; Koulouvaris, P. (Sports Biomechanics, 2023)
Aim of the study was to compare the isometric strength of flexors and extensors trunk muscles between male and female elite adolescent athletes of different age and training experience. Absolute and relative trunk muscle isometric peak extension (PTE) and flexion (PTF) torque, as well as flexion/extension (F/E) ratio were evaluated in 388 elite adolescent athletes 188 males (Age: 15.4±1.8 years, Body height: 175.5±11.2 cm, Body mass: 68.8±14.5 kg, BMI: 22.1±0.3 kg/m2) and 207 females (Age: 15.1±1.6 years, Body height: 166.8±7.8 cm, Body mass: 60.8±8.4 kg and BMI: 21.8±0.4 kg/m2). Participants were assigned into seven different groups according to their sport specialisation (oars-paddle, swimming, contact-combat, team, racket, winter and mixed other sports). Significant effect of age (n2: 0.077-0.112, p < 0.05), gender (n2: 0.020-0.077; p < 0.05) and sport category factors (n2: 0.057-0.154. p <0.005) for absolute/relative PTE, PTF and F/E ratio was found. The highest values were observed in contact-combat and the lowest in mixed other sports groups. F/E ratio significantly differs between the age groups, especially in female athletes. The present data suggest that TMSs and F/E ratio are highly affected by age, gender and sports specialisation in high level trained adolescents.